Taurine ameliorates blood pressure and vascular function in patients with type 2 diabetes: Randomized, double-blind, placebo-controlled trial - Yingsha Li; Qianran Wang; Yi Liu; Qiang Li; Weijie Xia; Shaoyang Lin; Qian Yang; Alexandra Scholze; Zhigang Zhao; Hongbo He; Hexuan Zhang; Zhencheng Yan; et al. (iScience)
Summary: Peripheral arterial disease (PAD) significantly elevates the risk of cardiovascular events in patients with type 2 diabetes (T2D). The role of transient receptor potential canonical type 6 (TRPC6) channel mediated increased calcium entry have been identified on platelets from patients with T2D. It remains unknown whether taurine benefits vascular function in patients with T2D. Diabetic patients aged 60.0 ± 8.6 years in the taurine group, N = 82; and 59.1 ± 10.4 years in the placebo group, N = 83 were randomly enrolled and received either taurine (2.4 g/day) or placebo for 12 weeks. Compared to the placebo, taurine led to a significant reduction in systolic BP, and improvement of endothelium-dependent or -independent vasodilation and pulse wave velocity after taurine 12 weeks in patients with T2D. Taurine significantly inhibited the activation of platelet calcium influx in patients with T2D. Taurine may exert beneficial the effects on blood pressure and vascular dysfunction in patients with T2D.